2003
DOI: 10.2170/jjphysiol.53.281
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of HSP72 in Reloading Rat Soleus Muscle after Prolonged Hindlimb Unloading

Abstract: The hind-limb suspension is an established method to unload hind-limb muscles and is largely known to induce muscle fiber atrophy, especially in an antigravity slow soleus muscle. The ankle joints of rat are hyper-extended in response to hind-limb suspension, therefore, the soleus muscles are passively shortened and tension development is inhibited even when the active electromyogram (EMG) is present [1,2]. The hind-limb unloading (HU) changes the myosin heavy chain (MHC) phenotypes and contractile properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 30 publications
5
32
0
Order By: Relevance
“…It was also reported that the protein synthesis activity was suppressed in the soleus muscle following the hindlimb unloading by tail suspension (10). Furthermore, the expression of the heat shock protein (HSP), which is a molecular chaperone, decreased by the unloading of muscle (14,31). These results clearly indicate that load applied is an important factor for muscle plasticity.…”
mentioning
confidence: 82%
“…It was also reported that the protein synthesis activity was suppressed in the soleus muscle following the hindlimb unloading by tail suspension (10). Furthermore, the expression of the heat shock protein (HSP), which is a molecular chaperone, decreased by the unloading of muscle (14,31). These results clearly indicate that load applied is an important factor for muscle plasticity.…”
mentioning
confidence: 82%
“…In animal models of unloading there is a substantial decline in Hsp70 (Desplanches et al 2004;Lawler et al 2006;Oishi et al 2003b) and Hsp27p (Huey et al 2005;Huey et al 2004) content, suggesting they may play important roles in the maintenance of muscle mass. The role of Hsps as cytoprotective agents has shown promise.…”
Section: Therapeutic Implications Of Our Datamentioning
confidence: 99%
“…It has been reported that gravitational unloading as a result of actual spacefl ight [1][2][3] or of simulation model, i.e., hindlimb suspension [4][5][6][7], inhibits the antigravity activity of skeletal muscles and modulates the neuromuscular properties in rats. Fiber atrophy and a shift from the slowto the fast-twitch phenotype in the fibers of rat skeletal muscles, predominantly in the antigravity slow-twitch muscles, are observed following hindlimb suspension [8].…”
mentioning
confidence: 99%